2023
DOI: 10.1038/s41597-023-02050-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution livestock seasonal distribution data on the Qinghai-Tibet Plateau in 2020

Abstract: Incorporating seasonality into livestock spatial distribution is of great significance for studying the complex system interaction between climate, vegetation, water, and herder activities, associated with livestock. The Qinghai-Tibet Plateau (QTP) has the world’s most elevated pastoral area and is a hot spot for global environmental change. This study provides the spatial distribution of cattle, sheep, and livestock grazing on the warm-season and cold-season pastures at a 15 arc-second spatial resolution on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Precipitation and land surface temperature can reflect climatic differences in different regions. These environmental variables directly affect vegetation growth and indirectly influence livestock distribution by determining the availability of fodder and water in a given area 41 , 42 . Settlement density also reflects the aggregation of livestock density.…”
Section: Methodsmentioning
confidence: 99%
“…Precipitation and land surface temperature can reflect climatic differences in different regions. These environmental variables directly affect vegetation growth and indirectly influence livestock distribution by determining the availability of fodder and water in a given area 41 , 42 . Settlement density also reflects the aggregation of livestock density.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental variables, such as precipitation, temperature, solar radiation, and vapor pressure deficit, were included to reflect climatological differences across regions. These environmental variables directly affect vegetation growth and indirectly impact livestock distribution by determining feed and water availability in a given area 36 , 37 , 48 . Additionally, the distance to settlements and water bodies was included as high-productive forage close to residential areas, and water bodies are more convenient for herders to allow livestock to graze 21 , 37 .…”
Section: Methodsmentioning
confidence: 99%
“…The lack of management practices determines the greater sensitivity to warming in grassland-based system because some indoor alleviations, like shed shade, shower and house heating control (Hristov et al, 2018;Toghiani et al, 2020), cannot be applied. In addition, compared with the cropland-feed system, the rangeland vegetation productivity is also more sensitive to climate change (Lehnert et al, 2016;Sloat et al, 2018;Weindl et al, 2015;Zhan et al, 2023) Moreover, the unequal burdens of warming are found across the countries with different income levels (defined by World Bank) and economic production. Specifically, the low-income countries are more vulnerable to the effect of warming.…”
Section: The Nonlinear Response Of Cattle Meat Yield To Warmingmentioning
confidence: 99%